Variação sazonal da comunidade protozooplanctônica em um ambiente oligotrófico tropical (reservatório de Ilha Solteira, Brasil) - Mansano, A. S.; Hisatugo, K. F.; Leite, M. A. [UNESP]; Luzia, A. P.; Regali-Seleghim, M. H. (FapUNIFESP (SciELO), 2013)
The seasonal variation of the protozooplanktonic community (ciliates and testate amoebae) was studied in a tropical oligotrophic reservoir in Brazil, which was under the influence of two contrasting climatic seasons (rainy/warm and dry/cold). The aim of this study was to evaluate the effect of these climatic changes on physical, chemical and biological variables in the dynamic of this community. The highest mean density of total protozoans occurred in the rainy/warm season (5683.2 ind L-1), while the lowest was in the dry/cold (2016.0 ind L-1). Considering the seasonal variations, the protozoan groups that are truly planktonic, such as the oligotrichs (Spirotrichea), predominated in the dry season, whereas during the rainy season, due to the material input and resuspension of sediment, sessile protozoans of the Peritrichia group were the most important ones. The dominant protozoans were Urotricha globosa, Cothurnia annulata, Pseudodifflugia sp. and Halteria grandinella. The highest densities of H. grandinella were associated with more oxygenated and transparent water conditions, while the highest densities of C. annulata occurred in sites with high turbidity, pH and trophic state index (TSI). The study demonstrated that density and composition of protozooplanktonic species and groups of the reservoir suffered seasonal variation due to the environmental variables (mainly temperature, turbidity, water transparency, dissolved oxygen and TSI) and the biological variables (e.g. morphological characteristics, eating habits and escape strategies from predation of the species).
Seasonal variation of the protozooplanktonic community in a tropical oligotrophic environment (Ilha Solteira reservoir, Brazil)
Keywords: Ciliates; Freshwater; Protozoans; Testate amoebae